1985
DOI: 10.1007/bf00165168
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal tumours of the cerebrum

Abstract: Eighteen cases of cerebral tumour composed partly or totally of primitive embryonal cells are reported. These lesions comprise 2.8% of all primary cerebral hemisphere tumours in the histopathology files of The Royal Marsden Hospital between 1971 and 1980 inclusive. Most exhibited some degree of differentiation towards neuronal or glial elements and, as more than one type of differentiation was often present in the same lesion, we agree with others that the term primitive neuroectodermal tumour (PNET) is more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 17 publications
1
75
0
Order By: Relevance
“…They comprise 3-7 % of brain tumors in children and young adults [1][2] and are associated with a dismal prognosis [3][4]. Histologically, these highly proliferative lesions are currently divided into CNS-PNET or supratentorial PNET, respectively (synonym PNET not otherwise specified, PNET NOS), CNS neuroblastoma, CNS ganglioneuroblastoma, medulloepithelioma, and ependymoblastoma [5].…”
Section: Introductionmentioning
confidence: 99%
“…They comprise 3-7 % of brain tumors in children and young adults [1][2] and are associated with a dismal prognosis [3][4]. Histologically, these highly proliferative lesions are currently divided into CNS-PNET or supratentorial PNET, respectively (synonym PNET not otherwise specified, PNET NOS), CNS neuroblastoma, CNS ganglioneuroblastoma, medulloepithelioma, and ependymoblastoma [5].…”
Section: Introductionmentioning
confidence: 99%
“…PNETs resemble classical medulloblastomas in several respects, such as histological appearance, occurrence in children and malignant behaviour (Gaffney et al 1985). Apart from the localisation respectively above and below the tentorium, differences between these two tumours consist of the most prevalent type of cell differentiation (astrocytic in PNETs vs neuronal in medulloblastomas), the capacity to seed along the cerebrospinal axis (15% vs 50%) (Albright et al 1995), and the response to surgical and radiation therapy (25% vs 50% 5-year survival rate) (Gaffney et al 1985).…”
Section: Discussion Definitionmentioning
confidence: 99%
“…Embryonic CNS tumours, consisting of less than 90% of undifferentiated cells and arising above the tentorium (i.e. not in the cerebellum) in patients of all ages, may thus be classified as PNET (Gaffney et al 1985).…”
Section: Discussion Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative RT is indicated for the embryonal CNS tumors. Classic studies indicate disease control in fewer than 25% of cases with sPNET and pineoblastoma (58,63). A review of the SIOP/UKCCSG experience showed high rates of disease control with cranio spinal irradiation (CSI) for pineoblastomas with or without CT.…”
Section: Therapymentioning
confidence: 99%